Factors Associated With Community Corrections Involvement Among Formerly Incarcerated People in Recovery - Chavira, Dina (Criminal justice policy review, 2018)
The current study examined whether current community supervision status was associated with differences in demographic characteristics, lifetime substance use patterns, and criminal history among a sample of formerly incarcerated individuals with a history of substance use problems. Results of multivariate analyses revealed participants on community supervision were more likely to have graduated from high school or earned a General Education Development test credential (GED; odds ratio [OR] = 1.60; 95% confidence interval [CI] = [0.15, 17.24]) and were less likely to have a history of psychiatric hospitalization (OR = 0.88; 95% CI = [0.08, 9.35]). These characteristics may be proxies for social and emotional functioning that influence eligibility for community supervision. Despite these apparent advantages, the community supervision group did not significantly differ from the formerly incarcerated group without current justice involvement on lifetime substance use patterns or criminal history, suggesting formerly incarcerated individuals with substance use disorders may require more intensive interventions to promote existing strengths.